Assessment sharing intra-industry strategic alliances: Effects on sustainable supplier management within multi-tier supply chains - Lechler, Sabrina; Canzaniello, Angelo; Hartmann, Evi (International Journal of Production Economics, 2019)
Focal companies have to manage both first-tier suppliers and lower-tier suppliers in order to prevent reputational damage due to sustainability violations in their supply chains. However, the involvement of sub-suppliers in supplier management practices creates new challenges, which can be managed more effectively in collaboration with other firms. Therefore, the purpose of this study is to explore from an extended agency theory perspective how companies collaborate within assessment sharing strategic alliances (ASSAs) to manage suppliers with respect to sustainability and to reveal the resultant effects on the management of suppliers within multi-tier supply chains. Therefore, an embedded multiple case study with multiple units of analysis was conducted. Results show that, dependent on the experience in ASSAs, supplier assessment and optionally supplier collaboration practices are executed collaboratively among the members of those strategic alliances to improve suppliers' compliance with the focal company's corporate sustainability standards. However, the configuration of jointly executed activities as well as membership conditions vary between strategic alliances and consequently influence the effects on supplier management. Nevertheless, the observations revealed that the causes for agency risk, namely information asymmetry and goal conflicts, can be mitigated through collaboration within ASSAs and thus multi-tier suppliers' compliance with corporate sustainability standards is fostered.
CRIS-Team Scopus Importer:2019-11-01
Keywords: Agency theory; Lower-tier supplier; Multi-tier supply chain management; Multiple case study design; Strategic alliance; Sub-supplier